2016
DOI: 10.1007/s13402-016-0311-7
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A-p53 mediated antitumor effect of Lupeol in head and neck cancer

Abstract: Together, our data indicate that Lupeol may orchestrate a bifurcated regulation of neoplastic growth and apoptosis in head and neck cancers and may serve as a promising agent for the management of tumors that have progressed on a platinum-based treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…This is an indication that lupeol is absorbed, metabolized and finally distributed in the tissues in which it can exert its beneficial effects. Several studies have shown that lupeol supplementation is able to reduce damage to organs such as kidneys (Sudhahar et al, ) and liver (Kim et al, ); to show anti‐inflammatory activities against inflammation‐related molecules such as cytokines involved in systemic inflammation such as tumor necrosis factor‐ α , interleukin‐1 β , interleukin‐2, interleukin‐4, interleukin‐6, interferon‐ γ or derivatives of arachidonic acid such as prostaglandin E2 (Siddique & Saleem, , and references therein), and anti‐cancer effects such as anti‐topoisomerase 2 (Sánchez‐Burgos et al, ); to down‐regulate pathways related to cancer development such as AKT/ERK (Liu et al, ); and to enhance expression of p53 and phase G1 cell cycle arrest (Bhattacharyya et al, ). Furthermore, lupeol shows few toxic effects associated with its consumption (Saleem, ), making it a good candidate for its potential use as a therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…This is an indication that lupeol is absorbed, metabolized and finally distributed in the tissues in which it can exert its beneficial effects. Several studies have shown that lupeol supplementation is able to reduce damage to organs such as kidneys (Sudhahar et al, ) and liver (Kim et al, ); to show anti‐inflammatory activities against inflammation‐related molecules such as cytokines involved in systemic inflammation such as tumor necrosis factor‐ α , interleukin‐1 β , interleukin‐2, interleukin‐4, interleukin‐6, interferon‐ γ or derivatives of arachidonic acid such as prostaglandin E2 (Siddique & Saleem, , and references therein), and anti‐cancer effects such as anti‐topoisomerase 2 (Sánchez‐Burgos et al, ); to down‐regulate pathways related to cancer development such as AKT/ERK (Liu et al, ); and to enhance expression of p53 and phase G1 cell cycle arrest (Bhattacharyya et al, ). Furthermore, lupeol shows few toxic effects associated with its consumption (Saleem, ), making it a good candidate for its potential use as a therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…75,76 They have used this platform with head and neck squamous cell carcinomas (HNSCC) and colorectal carcinomas (CRC) and evaluated responses to cytotoxic and targeted therapies by immunohistochemical assessment of cell death or proliferation biomarkers as well as pharmacodynamic biomarkers. 77,78 Strong correlations between CANScript responses to cytotoxic drug regimens of docetaxel, cisplatin and 5fluorouracil (TPF) and the responses of PDX models derived from the same human tumour samples to the same chemotherapies were observed. Furthermore, following stratification of HNSCCs for KRAS mutation status, correlations between the CANScript and PDX responses were observed upon treatment with the epidermal growth factor receptor (EGFR) inhibitor cetuximab.…”
Section: Recent Advances In Pde-based Platformsmentioning
confidence: 99%
“…head and neck, colorectal, prostate, pancreatic, and cervical cancer (Liu et al, 2015;Bhattacharyya et al, 2017;Emanuele et al, 2018;Wang et al, 2018b) inhibiting metastasis BCL2, CLAUDIN1, MMP2/9, MTCO2, NFKB, RELA, TP53…”
Section: Phenolic Acidsmentioning
confidence: 99%